Mestizaje, concubinato e ilegitimidad en la provincia de Costa Rica, 1690-1821. - Acuña León, María de los Ángeles (2012)
It is the interest of this work to analyze the dynamics of two of the primary mechanisms of the miscegenation, concubinage and the illegitimacy, in the particular case of the province of Costa Rica in the period 1690-1821, that corresponds to the called second colonial configuration that is framed between the aim of the era of the encomienda and until independence. The protagonists of this process were men and women of mixed blood, who were related in the cities and the ranches, to each other and with the other groups of the society, Indians, African slaves and Spanish, tie by bows of blood, social networks, networks of compadrazgo and economic relations. Consequently, the miscegenation is established as a characteristic not only of the yesterday Hispano-American colonial societies, but also of the today Latin American contemporary societies.